2017
DOI: 10.1002/app.46117
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun poly(vinyl alcohol)/permutite fibrous film loaded with cinnamaldehyde for active food packaging

Abstract: Electrospun ultra-fine poly(vinyl alcohol)/permutite fibrous film loaded with cinnamaldehyde essential oil was successfully fabricated.The morphology of fibrous filmswas characterized by scanning electron microscopy (SEM) and atomic force microscope (AFM). The fibrous film exhibited microstructure features with high porosity with the pore size distributed ranging from 1.7 nm to 56.7 nm. And the root-mean-squared roughness of fibers lifted to 546.5 nm when the addition of cinnamaldehyde essential oil (CEO) reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 44 publications
(41 reference statements)
1
9
0
Order By: Relevance
“…e study suggested that the concentration of antimicrobial agent consisting 2% CEO and 0.25% LYS (w/w) in PVA matrix has a decent performance as food packaging material. Shao et al fabricated ultrafine PVA/permutite/CEO membranes via electrospinning [105]. PVA doped with permutite powder was applied as polymer matrix and CEO was encapsulated as the antibacterial component.…”
Section: Essential Oil Combinationsmentioning
confidence: 99%
“…e study suggested that the concentration of antimicrobial agent consisting 2% CEO and 0.25% LYS (w/w) in PVA matrix has a decent performance as food packaging material. Shao et al fabricated ultrafine PVA/permutite/CEO membranes via electrospinning [105]. PVA doped with permutite powder was applied as polymer matrix and CEO was encapsulated as the antibacterial component.…”
Section: Essential Oil Combinationsmentioning
confidence: 99%
“…Recent laboratories have incorporated new nanomaterials to create what is called ESN-based chemical and hybrid biosensors, which have been applied in the agri-food sector to address food quality and safety [ 148 , 149 , 150 ]. The conjugated use of polymer, ceramic, and inorganic other materials are reviewed by Mercante et al [ 151 ]. In another branch of this very fertile sector, researchers used biocompatible ESN to entrap bioactive food ingredients, both hydrophilic and hydrophobic types [ 152 ].…”
Section: Potential Applications Of Electrospun Nanofiber Scaffoldsmentioning
confidence: 99%
“…At high humidity, pores can be formed on the fiber surface (Casper, Stephens, Tassi, Chase, & Rabolt, 2004). Most of them studies report, that increasing the humidity, caused an increase in the number, diameter and distributed size pores (Cheng, Qin, Hu, Yu, & Zhu, 2017; Ramakrishnan et al., 2019; Shao, Yan, Chen, & Xiao, 2018).…”
Section: Properties Of Electrospun Nanofibersmentioning
confidence: 99%